2016
DOI: 10.3892/etm.2016.3852
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting is neuroprotective in focal cerebral ischemia by minimizing autophagic flux disturbance and inhibiting apoptosis

Abstract: Previous studies have demonstrated that autophagy induced by caloric restriction (CR) is neuroprotective against cerebral ischemia. However, it has not been determined whether intermittent fasting (IF), a variation of CR, can exert autophagy-related neuroprotection against cerebral ischemia. Therefore, the neuroprotective effect of IF was evaluated over the course of two weeks in a rat model of focal cerebral ischemia, which was induced by middle cerebral artery occlusion and reperfusion (MCAO/R). Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Several studies have demonstrated a neuroprotective role for autophagy in acute hypoxic/ischaemic brain injury 26 , 27 . Hypoxia caused by compromised blood supply results in phosphorylation and activation of AMPK, which can also suppress phosphorylation of mTOR, can directly or indirectly promote autophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a neuroprotective role for autophagy in acute hypoxic/ischaemic brain injury 26 , 27 . Hypoxia caused by compromised blood supply results in phosphorylation and activation of AMPK, which can also suppress phosphorylation of mTOR, can directly or indirectly promote autophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic structures and/or markers are consistently observed in brain tissue derived from rodent models of acute hypoxic/ischemic brain injury [40,41]. However, controversy exists as to whether autophagy plays a protective or toxic role since both the positive [42,43] and the negative [41,43] modulation of autophagy has been reported to promote neuroprotection using in vivo models of brain ischemia. For instance, genetic silencing of Tuberous Sclerosis Complex 1 (TSC-1), which results in MTORC1 activation and the inhibition of autophagy, exacerbates neuronal injury using in vitro and in vivo models of transient global ischemia [44].…”
Section: Autophagy In the Central Nervous System (Cns)mentioning
confidence: 99%
“…Animals were fed commercially available rodent normal diet or IF (24 h fasting and 24 h feeding) was applied for 2 months according to method by published methods ( 9 , 12 , 17 ). During procedures, food intake of IF group was controlled daily (10 g per day), and body weight of normal diet and IF groups was monitored every week.…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al ( 11 ), have reporetd that IF protects hippocampal neurons against kainate excitotoxicity in a mouse model of Alzheimer's disease (presenilin1 mutant knockin mice) by reducing oxidative stress. In ischemia, it has been demonstrated that dietary restriction or an IF regimen reduces infarct volume in rodent models of cerebral focal cerebral ischemia by inhibiting the accumulation of autophagosomes in neurons ( 12 ), by suppressing inflammasome activity ( 13 ), and by increasing a preconditioning stress response ( 14 ). The above-mentioned studies attenuate or protect ischemic damage in focal cerebral ischemia models; however, the possibility that IF protects neurons from transient global cerebral ischemia (tGCI) has not been examined.…”
Section: Introductionmentioning
confidence: 99%